(untitled) (Revista Rupturas, 2018)
In Argentina, the women’s, feminist and LGBTI movements struggle to reform the law managed to dispute the conservative sexual order sustained by religious power and imbricated in the legal discourse. These reform processes, however, are resisted by conservative religious activism in different institutional instances with the purpose of (re) instituting conservative religious morality in the legal discourse. This article focuses on the interventions of pro-life NGOs and lawyers in the judicial processes with the purpose of obstructing, preventing and / or criminalizing access to abortion in Argentina. The study of these processes allows us to expand the understanding of one of the main strategies of religious conservatism in Latin America, the use of litigation to resist the current legal reforms.